2015
DOI: 10.1186/s12943-015-0433-y
|View full text |Cite
|
Sign up to set email alerts
|

Invasion of ovarian cancer cells is induced byPITX2-mediated activation of TGF-β and Activin-A

Abstract: BackgroundMost ovarian cancers are highly invasive in nature and the high burden of metastatic disease make them a leading cause of mortality among all gynaecological malignancies. The homeodomain transcription factor, PITX2 is associated with cancer in different tissues. Our previous studies demonstrated increased PITX2 expression in human ovarian tumours. Growing evidence linking activation of TGF-β pathway by homeodomain proteins prompted us to look for the possible involvement of this signalling pathway in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
71
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 64 publications
(71 citation statements)
references
References 56 publications
0
71
0
Order By: Relevance
“…Immunofluorescence was carried out as described previously [30] using the antibodies Claudin 7, Vimentin, Snail and β-catenin.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Immunofluorescence was carried out as described previously [30] using the antibodies Claudin 7, Vimentin, Snail and β-catenin.…”
Section: Methodsmentioning
confidence: 99%
“…Previous reports suggest that Wnt and TGFβ promote EMT [27-29]. Considering background references regarding Wnt and TGFβ signalling cascades in EMT and ovarian cancer [28-30], we wanted to study the effect of this co-activation in these processes to mimick a part of the signalling cascade functioning in the tumour microenvironment. In this report, we have shown the effect of the functioning of Wnt and TGFβ in unison in abrogating EMT.…”
Section: Introductionmentioning
confidence: 99%
“…Immunofluorescence staining with E-cadherin and N-cadherin (1: 100) antibodies followed by Alexafluor 488-conjugated secondary antibody was performed as described previously [22]. For phalloidin staining 10 5 cells/well were treated and the cellular morphology was observed as mentioned previously [23].…”
Section: Methodsmentioning
confidence: 99%
“…The role of activin A in epithelial ovarian cancer is less clear. Basu et al observed higher phospho-Smad2 immunostaining in ovarian tumors compared to normal ovaries [32], and Do et al found that ovarian cystadenocarinoma patients with high immunostaining for INHBA tended to have shorter survival times than patients with low immunostaining [33]. Activin A stimulates migration of OCC1 and SKOV3 cells [34].…”
Section: Introductionmentioning
confidence: 99%